Allelopathic activity of Manihot esculenta crantz on the germination of Avena sativa L. and Trifolium resupinatum L. Seeds - Stefanello, Raquel; Menna Barreto, Rafaelle Almeida; Garcia, Wagner Jesus da Silva; Dorneles, Lucio Strazzabosco (Disciplinarum Scientia | Naturais e Tecnológicas, 2024)
Allelopathy can be considered a chemical interference of one or more substances from a plant species in the development of another species, encompassing both inhibition and stimulation effects. In this context, the goal of the research was to evaluate the allelopathic effect of Manihot esculenta (cassava) leaf extracts on white oat and Persian clover seed germination. The seeds were placed on germitest paper containing leaf extract at concentrations corresponding to 0, 25, 50, 75, and 100% and kept in a germination chamber at 20 °C in the presence of light. The results showed that M. esculenta extracts negatively affected the germination and initial growth of white oat and Persian clover seedlings. Thus, as an adequate management practice, it is recommended that M. esculenta leaves be removed from the fields before sowing in order to avoid a negative influence on the initial growth of these species.